SARS-CoV-2 Mutations and Variants May Muddle the Sensitivity of COVID-19 Diagnostic Assays - Mohammad Alkhatib; Luca Carioti; Stefano D’Anna; Francesca Ceccherini-Silberstein; Valentina Svicher; Romina Salpini (Microorganisms, 2022)
The performance of diagnostic polymerase chain reaction (PCR) assays can be impacted by SARS-CoV-2 variability as this is dependent on the full complementarity between PCR primers/probes and viral target templates. Here, we investigate the genetic variability of SARS-CoV-2 regions recognized by primers/probes utilized by PCR diagnostic assays based on nucleotide mismatching analysis. We evaluated the genetic variation in the binding regions of 73 primers/probes targeting the Nucleocapsid (N, N = 36), Spike (S, N = 22), and RNA-dependent RNA-polymerase/Helicase (RdRp/Hel, N = 15) of the publicly available PCR-based assays. Over 4.9 million high-quality SARS-CoV-2 genome sequences were retrieved from GISAID and were divided into group-A (all except Omicron, >4.2 million) and group-B (only Omicron, >558 thousand). In group-A sequences, a large range of variability in primers/probes binding regions in most PCR assays was observed. Particularly, 87.7% (64/73) of primers/probes displayed ≥1 mismatch with their viral targets, while 8.2% (6/73) contained ≥2 mismatches and 2.7% (2/73) contained ≥3 mismatches. In group-B sequences, 32.9% (24/73) of primers/probes were characterized by ≥1 mismatch, 13.7% (10/73) by ≥2 mismatches, and 5.5% (4/73) by ≥3 mismatches. The high rate of single and multiple mismatches- found in the target regions of molecular assays used worldwide for SARS-CoV-2 diagnosis reinforces the need to optimize and constantly update these assays according to SARS-CoV-2 genetic evolution and the future emergence of novel variants.